Relaciones entre automatización avanzada y empleo: El caso de la industria autopartista en Argentina - Carlos Andrés Pan (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
– The developments in technology within the framework of what is known as Industry 4.0, due to their disruptive nature, raise questions about the impact they will have on employment. The automotive industry is experiencing a paradigm shift towards new forms of connectivity, autonomy, ownership and propulsion that are giving rise to a new approach to business throughout the world. In this environment, this research work aims to investigate the potential courses of action for the survival and growth of auto parts makers in Argentina facing the 2021-2030 period, in the light of automation developments, considering them from their perspective as a socio-technical system, and involving labor-technological relations and the availability of the necessary capacities and abilities
Keywords: O0; 330; Automatización; robótica; sistema socio-técnico; sindicatos; relacioneslaborales; industria 4.0